High efficient removal of molybdenum(VI) from aqueous solution by starch-acrylamide/nanohalloysite composite. (November 2022) - Elsharma, Emad M.; Emara, Amr M.; Abdelmonem, Islam M.; Gizawy, Mohamed A.
Abstract: In this paper, poly(starch-acrylamide/nanohalloysite) [P(St-AAm/NH)] was prepared by grafting acrylamide onto starch using gamma rays as an initiator. Physical characteristics of the newly synthesized nanocomposite were studied using FT-IR, TGA, DTA and SEM. P(St-AAm/NH) was evaluated for adsorption of Mo(VI) radionuclide from aqueous solution using batch sorption experiments. Factors affecting adsorption of Mo(VI) radionuclide, such as pH, contact time, and metal ion concentration were extensively investigated. P(St-AAm/NH) composite shows high sorption capacity of 524 mg g −1 towards Mo(VI) radionuclide. Finally, Mo(VI) radionuclide sorption was best represented by the pseudo-second-order kinetic model. As well, it was best fitted to Langmuir model, which suggests the chemisorption mechanism. Graphical abstract: Image 1 Highlights: Starch-acrylamide/halloysite nanocomposite was prepared by gamma irradiation grafting technique. Gamma-irradiation renders a higher grafting efficiency of the nanocomposite. High adsorption capacity of the nanocomposite toward molybdenum radionuclide was shown.